Birthplace diversity and productivity spill-overs in firms - René Böheim; Thomas Horvath; Karin Mayr (Johannes Kepler University Linz, NRN - The Austrian Center for Labor Economics and the Analysis of the Welfare State, 2014)
We determine workforce composition and wages in firms in the presence of productivity spill-overs between co-workers. In equilibrium, workers' wages depend on the production struc- ture of firms, own group size, and aggregate workforce composition in the firm. We estimate the wage effects of workforce diversity and own group size by birthplace and the implied pro- duction structure in Austrian firms using a comprehensive matched employer-employee data set. In our data, we identify a positive effect of workforce diversity and a negative effect of own group size on wages, which suggest that workers of different birthplaces are complements in production on average.
Keywords: D21; D22; F22; J31; 330